2019
DOI: 10.1016/j.jpedsurg.2019.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of MYCN protein by CX-5461 leads to neuroblastoma tumor growth suppression

Abstract: Purpose: MYCN oncogene amplification is an independent predictor of poor prognosis in neuroblastoma. CX-5461 is a small molecular inhibitor that prevents initiation of ribosomal RNA (rRNA) synthesis by RNA Pol I, down-regulating MYCN/MYC proteins. We hypothesize that neuroblastoma tumor growth can be suppressed by CX-5461. Methods: MYCN-amplified (KELLY, IMR5) and non-amplified (SY5Y, SKNAS) neuroblastoma cells were treated with CX-5461. MYCN/MYC expression after 24-48 hours was determined by Western blot. Ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Indeed, results from the first-in-human clinical trial for CX-5461 strongly suggests that a functional p53 protein is a potential biomarker for treatment outcome. Although the number of patients in this study was limited, patients with WT p53 appear to respond better to the treatment [93]. In solid tumours, the response to Pol I transcription inhibition does not appear to correlate with p53 status, although increased sensitivity to Pol transcription inhibitors is also observed in some p53 WT tumours [56,88].…”
Section: Patient Stratificationmentioning
confidence: 81%
See 1 more Smart Citation
“…Indeed, results from the first-in-human clinical trial for CX-5461 strongly suggests that a functional p53 protein is a potential biomarker for treatment outcome. Although the number of patients in this study was limited, patients with WT p53 appear to respond better to the treatment [93]. In solid tumours, the response to Pol I transcription inhibition does not appear to correlate with p53 status, although increased sensitivity to Pol transcription inhibitors is also observed in some p53 WT tumours [56,88].…”
Section: Patient Stratificationmentioning
confidence: 81%
“…CX-5461 has recently completed a Phase I clinical trial in patients with advanced haematological cancers [93]. In this first-in-human, phase I dose-escalation study, CX-5461 was determined safe and the maximum tolerated dose was identified.…”
Section: Selective Inhibitors Of Pol I Transcriptionmentioning
confidence: 99%
“…In recent years, several small molecule cytotoxic drugs have been identified as specific inhibitors of ribosome biogenesis ( 8–10 ). CX-5461 is one such drug that has also demonstrated anticancer potential for a wide range of malignancies ( 9 , 11–23 ), and is presently under phase I trials for the treatment of both haematological cancers and solid tumours ( 24 , 25 ). CX-5461 was initially characterized as an inhibitor of the transcription of the ribosomal RNA genes (rDNA) by RNA polymerase I (RPI/PolR1/PolI) ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors that downregulate MYCN/MYC proteins can suppress N.B. tumor growth [ 22 ]. Mutations in the tyrosine kinase domain of Anaplastic lymphoma kinase ( ALK ) have also been identified in N.B.…”
Section: Discussionmentioning
confidence: 99%